Passive Proselytism: The European Court of Human Rights and Religious Garments - Carpenter, Christine (Journal of law, religion and state, 2021)
Abstract Article 9 of the European Convention on Human Rights protects the right to freedom of religion and conscience. The language of Article 9(1) has been interpreted by the European Court of Human Rights as including protections for acts of proselytism, when properly committed and respectful of the rights and freedoms of others. This was the view taken in the foundational Article 9 case of the Court, Kokkinakis v. Greece. In the decades since Kokkinakis, however, the view of the Court on proselytism appears to have shifted, in particular in Article 9 cases involving religious garments. This article seeks to determine whether the Court is consistent in its views on proselytism between these religious garment cases and earlier examples of Article 9 case law.